Third Gender Marking in Spanish: Evaluation of Current Options from a Linguistic Change Point of View - Irene Checa-García (Ex Aequo: Revista da Associação Portuguesa de Estudos sobre as Mulheres)
Several proposals have been presented to make Spanish more inclusive in recent decades. In the case of inclusive language for a third gender, different groups advocate for new suffixes, such as <-@, -*, -x, -e, and -i>. In this work, I suggest that an option aligned with general trends in linguistic change is more likely to succeed, although intentional language planning will likely still be needed. Characteristics of a more easily adoptable third-gender suffix are presented, and each potential suffix is evaluated to determine which could be more successful from the perspective of linguistic change.